Genotyping and Plasma/Cerebrospinal Fluid Profiling of a Cohort of Frontotemporal Dementia–Amyotrophic Lateral Sclerosis Patients - Mara Bourbouli; George P. Paraskevas; Mihail Rentzos; Lambros Mathioudakis; Vasiliki Zouvelou; Anastasia Bougea; Athanasios Tychalas; Vasilios K. Kimiskidis; Vasilios Constantinides; Spiros Zafeiris; Minas Tzagournissakis; Georgios Papadimas; et al. (Brain Sciences, 2021)
Frontotemporal dementia (FTD) and amyotrophic lateral sclerosis (ALS) are part of the same pathophysiological spectrum and have common genetic and cerebrospinal fluid (CSF) biomarkers. Our aim here was to identify causative gene variants in a cohort of Greek patients with FTD, ALS and FTD-ALS, to measure levels of CSF biomarkers and to investigate genotype-phenotype/CSF biomarker associations. In this cohort of 130 patients (56 FTD, 58 ALS and 16 FTD-ALS), we performed C9orf72 hexanucleotide repeat expansion analysis, whole exome sequencing and measurement of “classical” (Aβ42, total tau and phospho-tau) and novel (TDP-43) CSF biomarkers and plasma progranulin. Through these analyses, we identified 14 patients with C9orf72 repeat expansion and 11 patients with causative variants in other genes (three in TARDBP, three in GRN, three in VCP, one in FUS, one in SOD1). In ALS patients, we found that levels of phospho-tau were lower in C9orf72 repeat expansion and MAPT c.855C>T (p.Asp285Asp) carriers compared to non-carriers. Additionally, carriers of rare C9orf72 and APP variants had lower levels of total tau and Aβ42, respectively. Plasma progranulin levels were decreased in patients carrying GRN pathogenic variants. This study expands the genotypic and phenotypic spectrum of FTD/ALS and offers insights in possible genotypic/CSF biomarker associations.